Opioid receptors in GtoPdb v.2021.3. (2021) - Borsodi, Anna; Bruchas, Michael; Caló, Girolamo; Chavkin, Charles; Christie, MacDonald J.; Civelli, Olivier; Connor, Mark; Cox, Brian M.; Devi, Lakshmi A.; Evans, Christopher; Höllt, Volker; Henderson, Graeme; et al.
No abstract available